2016
DOI: 10.1080/10550887.2016.1171670
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity to alcohol-related care among U.S. women Veterans with alcohol misuse

Abstract: Previous research indicates women Veterans have a potentially large, unmet need for alcohol-related care but are under-represented in treatment settings. The purpose of this study was to identify factors associated with women Veterans' receptivity to a recommendation for alcohol-related care when they present to Veterans Affairs (VA) primary care with alcohol misuse. Semi-structured interviews were conducted from 2012-2013 with 30 women Veterans at two VA facilities who screened positive for alcohol misuse dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…A recent review identified several barriers to women seeking help, including co‐occurring disorders, financial disparities and fear of child protective services [44]. Furthermore, outcomes for veteran and non‐veteran women are best when treatments for AUD are delivered in women‐only programs [44–46].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review identified several barriers to women seeking help, including co‐occurring disorders, financial disparities and fear of child protective services [44]. Furthermore, outcomes for veteran and non‐veteran women are best when treatments for AUD are delivered in women‐only programs [44–46].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 2 subsequent studies using national survey data have failed to replicate such gender differences in perceived need (Edlund et al., ; Grella et al., ); however, in 1 of those studies outcomes were not disaggregated between alcohol and drug treatment (Grella et al., ). A qualitative study of heavy drinking women attending Veterans Affairs medical centers found that perceptions of drinking—driven largely by perceived control over alcohol use and drinking‐related consequences—were the factor most frequently associated with alcohol services (Lewis et al., ). Given different legal statuses and social attitudes toward use, combining substance use treatments may obscure potentially important distinctions between men's and women's motivations and barriers by service type.…”
Section: Studies On Gender Differences In Alcohol Services Utilizationmentioning
confidence: 99%
“… 61 Female veterans receiving care at VAMCs offering specialized services for women were more likely to engage in treatment and were more receptive to SUD treatment when gender-specific care options were accessible. 64 , 65 …”
Section: Introductionmentioning
confidence: 99%